2021
DOI: 10.1038/s41598-021-97549-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of myeloid cell leptin signaling in the regulation of glucose metabolism

Abstract: Although innate immunity is linked to metabolic health, the effect of leptin signaling in cells from the innate immune system on glucose homeostasis has not been thoroughly investigated. We generated two mouse models using Cre-lox methodology to determine the effect of myeloid cell-specific leptin receptor (Lepr) reconstitution and Lepr knockdown on in vivo glucose metabolism. Male mice with myeloid cell-specific Lepr reconstitution (Lyz2Cre+LeprloxTB/loxTB) had better glycemic control as they aged compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Furthermore, IL-1 receptor I deficient mice have improved glucose tolerance and reduced inflammation in obesity, suggesting that macrophage production of IL-1β is a critical inflammatory driver in obesity [ 39 ]. A study investigating the role of leptin signaling in myeloid cells found that specific deletion of leptin receptor in myeloid cells did not significantly affect glycemic control [ 41 ]. However, selective reconstitution of leptin receptor in myeloid cells in mice that were otherwise leptin receptor deficient resulted in improved glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-1 receptor I deficient mice have improved glucose tolerance and reduced inflammation in obesity, suggesting that macrophage production of IL-1β is a critical inflammatory driver in obesity [ 39 ]. A study investigating the role of leptin signaling in myeloid cells found that specific deletion of leptin receptor in myeloid cells did not significantly affect glycemic control [ 41 ]. However, selective reconstitution of leptin receptor in myeloid cells in mice that were otherwise leptin receptor deficient resulted in improved glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a glucometer type should be used consistently in a given experiment ( Ayala et al 2010 , Togashi et al 2016 ) and its results are usually most reliable when glycemia is not excessively high ( Togashi et al 2016 , Morley et al 2018 ). When doing GTTs and PTTs in models of diabetes, plasma glucose concentrations can be determined after completion of the tests using a glucose assay kit ( Pereira et al 2021 ).…”
Section: Factors To Consider When Assessing Glucose Metabolism ...mentioning
confidence: 99%
“…Sex hormones also affect body composition (amount and distribution of fat tissue), which is an important determinant of insulin sensitivity ( Elbers et al 1999 , Macotela et al 2009 , Hocking et al 2013 ). The enhanced insulin sensitivity associated with being female often deteriorates in insulin-resistant states ( Tramunt et al 2020 , Pereira et al 2021 ).…”
Section: Factors To Consider When Assessing Glucose Metabolism ...mentioning
confidence: 99%